Can an early perceptuo-motor skills assessment predict future performance in youth table tennis players? An observational study (1998-2013) - Faber, I. R.; Elferink-Gemser, M. T.; Oosterveld, F. G. J.; Twisk, J. W. R.; Nijhuis-van der Sanden, M. W. G. (Journal of Sports Sciences, 2017)
This study intended to investigate the capability of the 4 test items "sprint", "agility", "speed while dribbling" and "throwing a ball" of the Dutch perceptuo-motor skills assessment used at the age of 7-10 years to predict table tennis performance (U13, U15 and U18) in an observational study. Data of 1191 young table tennis players, collected from 1998 to 2013, were analysed in univariable and multivariable logistic and linear regression models. The test items "sprint" and "throwing a ball" showed to be significant predictors for table tennis performance outcomes in boys (P < 0.05). For girls, besides these test items also "speed while dribbling" had a significant contribution (P < 0.05). Since the accuracies of the models were low, it is advised to include other determinants to enhance the predictive value of a model for table tennis performance. Nevertheless, it can be concluded that a perceptuo-motor skills assessment might improve the effectiveness of talent programmes in table tennis as an additional method to objectively estimate a youth players` potential. Future research focusing on the inclusion of test items specifically assessing eye hand coordination and other domains, for example, the psychological and the environmental domain, related to table tennis performance are recommended.